Pengaruh pembelajaran kewirausahaan dan motivasi wirausaha Terhadap niat berwirausaha - Utama, Dian Herdiana; Mulyadi, Hari; Disman, Disman; Imbragia, Sindi Tasya (Journal of Business Management Education (JBME), 2020)
The process of creating a new business is revealed from time to time, and the first stage is to have entrepreneurial intentions. A person's entrepreneurial intentions reflect their level of interest at the beginning of a business. The intention of entrepreneurship can also depend on external factors such as unfavorable economic factors and the difficulty of finding a job. The intention of entrepreneurship is important because it increases the confidence of employers that their work is meaningful, leads to a greater level of perseverance in business activities, increases creativity in problem solving, and increases ownership of experience related to business success and failure. One effort to increase the number of entrepreneurs is through education, namely entrepreneurship learning, besides that the motivation for entrepreneurship is one factor in supporting the increased intention of entrepreneurship.